Sleep disorders and their determinants in multiple system atrophy. Issue 6 (1st June 2002) - Ghorayeb, I; Yekhlef, F; Chrysostome, V; Balestre, E; Bioulac, B; Tison, F
Abstract : Objectives: To evaluate the incidence, types, determinants, and consequences of sleep disorders in patients with multiple system atrophy (MSA) and determine whether their characteristics are similar to those of patients with Parkinson's disease (PD). Methods: Information about sleep disorders was collected using a standardised questionnaire in an unselected group of 57 patients with MSA and in 62 patients with PD matched as a group for age, sex distribution, and disease duration. Results: Seventy percent of patients with MSA complained of sleep disorders compared with 51% of patients with PD (p=0.03). The most commonly reported sleep disorders were sleep fragmentation (52.5%), vocalisation (60%), REM sleep behaviour disorder (47.5%), and nocturnal stridor (19%). Except for sleep fragmentation, the incidence of these disorders was significantly higher than in PD. Sleep problems tended to be associated with more severe motor symptoms, longer disease duration, depression, and longer duration of levodopa treatment. Half of patients with MSA with sleep disorders complained of daytime somnolence compared with 30% of patients with PD. Daytime somnolence was significantly associated with disease severity in MSA. Conclusion: This study shows that sleep disorders are more common in patients with MSA than in those with PD after the same duration of the disease, reflecting the more diffuse underlying pathological process in MSA.